Prolonged CT urography in duplex kidney. Issue 1 (December 2016) - Gong, Honghan; Gao, Lei; Dai, Xi-Jian; Zhou, Fuqing; Zhang, Ning; Zeng, Xianjun; Jiang, Jian; He, Laichang
Abstract Background Duplex kidney is a common anomaly that is frequently associated with multiple complications. Typical computed tomography urography (CTU) includes four phases (unenhanced, arterial, parenchymal and excretory) and has been suggested to considerably aid in the duplex kidney diagnosi. Unfortunately, regarding duplex kidney with prolonged dilatation, the affected parenchyma and tortuous ureters demonstrate a lack of or delayed excretory opacification. We used prolonged-delay CTU, which consists of another prolonged-delay phase (1- to 72-h delay; mean delay: 24 h) to opacify the duplicated ureters and affected parenchyma. Methods Seventeen patients (9 males and 8 females; age range: 2.5–56 y; mean age: 40.4 y) with duplex kidney were included in this study. Unenhanced scans did not find typical characteristics of duplex kidney, except for irregular perirenal morphology. Duplex kidney could not be confirmed on typical four-phase CTU, whereas it could be easily diagnosed in axial and CT-3D reconstruction using prolonged CTU (prolonged-delay phase). Results Between January 2005 and October 2010, in this review board-approved study (with waived informed consent), 17 patients (9 males and 8 females; age range: 2.5 ~ 56 y; mean age: 40.4 y) with suspicious duplex kidney underwent prolonged CTU to opacify the duplicated ureters and confirm the diagnosis. Conclusion Our results suggest the validity of prolonged CTU to aid in the evaluation of the function of the affected parenchyma and in the demonstration of urinary tract malformations.